Contested Countryside: Rural Workers and Modern Society in Atlantic Canada, 1800-1950 - Little, J.i. (Labour / Le Travail, 1995)
The article reviews the book, "Contested Countryside: Rural Workers and Modern Society in Atlantic Canada, 1800-1950," edited by Daniel Samson.
Keywords: BOOKS -- Reviews; CONTESTED Countryside: Rural Workers & Modern Society in Atlantic Canada 1800-1950 (Book); Nonfiction; SAMSON, Daniel; SOCIAL development